PERBEDAAN LEMBAGA PENGAWAS PERSAINGAN USAHA DI INDONESIA DAN AUSTRALIA DALAM PENGAWASAN TERHADAP PERJANJIAN TERTUTUP: Differences in Competition Supervisory Agencies in Indonesia and Australia in the Overseeing Confidential Agreement - Ryan Wirangga Satya; Dian Purnamasari (Faculty of Law, Universitas Trisakti, 2025)
Exclusive dealing is an agreement entered into by one or more business actors with other businesses of a different tier. In Indonesia and Australia, each each has a competition watchdog that deals with all matters related to business competition, including including competition offences such as restrictive covenants exclusive dealing. Therefore, this research will discuss the differences between competition supervisory institutions in Indonesia and Australia. Type of research research type that will be used is normative type and descriptive in nature by using secondary data from primary, secondary, and tertiary legal materials. using secondary data from primary, secondary, and tertiary legal materials. Data data is collected through literature study and conclusions are drawn using the deductive method. deductive method. The results show that competition supervisory institutions in Indonesia and in Indonesia and Australia have differences in the form of licensing rules, approach in assessing violations, to the authority possessed by each business supervisory institution. business supervisory institution.